Light calvary - De la Costa, Horacio, 1916-1977 (Manila, Philippine : National Office of Mass Media, 1997)
Published by Catholic bishop Conference of the Philippines through National Office of Mass Media
Keywords: Jesuits -- Philippines -- History; Philippines -- Church history